Sharia in the Nigerian Constitutions: Examining the Constitutional Conferences and the Sharia Debates in the Drafts - Hasan-Bello, Abdulmajeed (Faculty of Shariah and Law, State Islamic University (UIN) Walisongo, 2019)
The paper examines the socio-ethnic and religious configuration of Nigeria and the nature of Sharia debates in the Nigeria constitutions of 1977/1978; 1988/1989 debates and Constitutional Conference of 1994/1995. The paper argues that the genesis of the Sharia debates can be traced to 1956. The Constitutional Conference of 1994/95 was not bedeviled by a serious acrimonious debate over the Sharia. However, the 1999 constitution brought a new dimension to the issue of the Sharia. To some extent, the enactment of Sharia law in Nigeria is a prime example of the relative success of Nigeria’s multi-state federalism in regards to governing diversity. Particularly the political autonomy to establish a Sharia Court of Appeal with civil jurisdiction on Islamic personal law. The paper concludes that the constitutionalization of the Sharia has subjected it to the vagaries of the political wind and made it easy prey to political fortune-seekers. Thus, the matters relating to religions should be removed from the future deliberative process in the country.